2013
DOI: 10.3126/hprospect.v12i1.8720
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding time and Clotting Time in Healthy Male and Female College Students of Karukutty Village, Kerala

Abstract: BackgroundIt was reported that females are having high Bleeding time and clotting time than males. The reason for prolonged bleeding and clotting time in females is not clear. The studies on Bleeding time and Clotting time in healthy male and female college students of Kerala are inadequate. Therefore the present study was undertaken to measure and compare bleeding time and clotting time in male and female college students. MethodologyTwo hundred and twenty two healthy male and female college students, were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(20 reference statements)
1
7
0
1
Order By: Relevance
“…These findings confirm those of Ikese et al (2015), who found that a freeze-dried extract of Tridax procumbens significantly decreased bleeding time. The results are also similar to the ethanolic extracts of the same plant that were shown to reduce the bleeding time (Manjusha et al 2014) which reflects platelet function (Kumar et al 2013). This plant has potential activation effects on the platelets.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These findings confirm those of Ikese et al (2015), who found that a freeze-dried extract of Tridax procumbens significantly decreased bleeding time. The results are also similar to the ethanolic extracts of the same plant that were shown to reduce the bleeding time (Manjusha et al 2014) which reflects platelet function (Kumar et al 2013). This plant has potential activation effects on the platelets.…”
Section: Discussionsupporting
confidence: 79%
“…These are new findings on this plant that have previously not been reported. Bleeding time indicates the platelet function (Kumar et al 2013), and therefore, this plant may have activation effects on the platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Similar findings of raised BT and CT were seen in females compared to males but was statistically significant in other studies. [17,22,26] There was no such difference in BT, CT gender-wise in study carried out by Mahapatra and Mishra. [20] ||CONCLUSIONS Blood group B is the most common blood group among the students and AB is the least common blood group.…”
Section: |Discussionmentioning
confidence: 84%
“…Karbon monoksida adalah gas beracun yang mempunyai afinitas kuat terhadap hemoglobin pada sel darah merah sehingga membentuk karboksi hemoglobin. 5,6 Paparan asap rokok yang dialami terusmenerus pada orang dewasa yang sehat dapat menambah risiko terkena penyakit paru-paru dan penyakit jantung sebesar 20-30 %. 7 Merokok merupakan salah satu faktor yang dapat menyebabkan peningkatan kadar homosistein plasma.…”
Section: Pendahuluanunclassified